Consortium of five fungal isolates conditioning root growth and arbuscular mycorrhiza in soybean, corn, and sugarcane - FARIAS,CHRISTYAN P. (2018)
Abstract Plant growth and arbuscular mycorrhizal colonization were studied in sugarcane, corn and soybean by applying five plant growth promoting fungi: Beauveria bassiana, Metarhizium anisopliae, Pochonia chlamydosporia, Purpureocillium lilacinum, and Trichoderma asperella. Sugarcane, corn and soybean were grown in pots under two treatments: (1) inoculation with the fungal consortium and (2) control without inoculation. In the inoculated treatment, fungal spore suspension were applied to the seeds and shoots were sprayed every 28 days. Means were analyzed by analysis of variance and Tukey’s test at 5% probability level. The experiment was arranged in a completely randomized design, with six replications. Fungi consortium mediate root growth in soybean and corn, and arbuscular mycorrhizal colonization in soybean and sugarcane. These findings are probably caused by the fungi producing phytohormones and inducing the plants to synthesize phytohormones: auxins for root growth; and jasmonic, abscisic, and salicylic acids with a role in the regulation of mycorrhizal colonization. These effects are important when seeking conservation strategies in agriculture and livestock production, since Fungi consortium can better mediate soil resource acquisition, promoting greater absorption of nutrients and water.